The effect of the US troop deployments on conflict initiation and diplomatic relations - Masjidi, Jahanzib (Kansas State University, 2021)
Since the end of the World War II, the United States has deployed hundreds of thousands of troops to foreign countries. The purpose of the US troop deployments is to deter adversaries, protect US allies, and to signal America’s commitment to a particular region. There is an emerging body of research that investigates the effects of the US troop deployments on the host state’s foreign policy. However, we still need to examine the influence of the US troop deployments on some other policy areas. In particular, the existing research does not explain how the US troop deployments affect the relations between the host states and their neighbors. Since US troop deployments have an effect on a range of issues in the host state, it is possible that these deployments might also have a positive or negative influence on the relations between the host state and its neighbors. Thus, it is important to examine whether the presence of US troops alter the behavior of the neighboring countries toward the host state. This study contributes to the scholarship about US troop deployments in two important ways. First, it examines how the deployment of US troops affect the likelihood of conflict onset between the host state and its neighboring state. Second, it investigates what impact do US troop deployments have on the diplomatic behavior of the host states and their neighbors. This thesis makes two central arguments: (1) the deployment of US troops represent a credible commitment by the US for the protection of the host state, which in turn decreases the likelihood of conflict initiation by the neighboring state against the host state, (2) US troop deployments can improve economic ties and cooperation between the host state and its neighbors, which make the neighboring countries prone to align with the host state on diplomatic issues. To empirically examine these propositions, this study examines the relationship between military deployments, conflict onset, and UN voting patterns.
Keywords: US troop deployments; Conflict; Diplomatic relations; Economic ties; Relations between the host states and their neighboring countries; Troop deployments